Technologcial progress and development directions of PetroChina overseas oil and gas exploration - Longxin MU; Zhifeng JI (Petroleum Exploration and Development, 2019)
Through a comprehensive review of PetroChina overseas oil and gas exploration of more than 20 years, we systematically summarize the development history, development status and application results of the overseas oil and gas exploration theory and technology. Overseas oil and gas exploration has experienced four stages, exploratory exploration, progressive exploration, risk exploration and efficient exploration. The overseas exploration theory and technology have also gone through the initially direct borrow of domestic mature technology to the integrated application, and then to the research innovation based on overseas features. A series of overseas oil and gas exploration theories and technologies represented by theories and technologies for passive rift basins, salt basins and foreland basin slopes, and global oil and gas geology and resource evaluation have been established. On the basis of deep analysis of the future overseas exploration development demand for the technology, and combined with the domestic and overseas future development trend of theory and technology, this paper systematically discusses the overseas exploration difficulties, technical requirements and the main development directions and aims of exploration theory and technology in the future: (1) Develop conventional onshore oil and gas exploration techniques continuously for the overseas exploration and keep them at an internationally advanced level. (2) Develop the global oil and gas resources and assets integrated optimization evaluation technology and its information system construction project innovatively to reach the international leading level. (3) Develop the deep water exploration technology integratively and narrow the gap with the world's advanced level. Key words: PetroChina, overseas oil and gas exploration, passive rift basin, salt basin, foreland basin, global petroleum resource assessment, exploration theory